2015
DOI: 10.1002/chem.201406617
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Chemoselective N‐1 Acylation of Indoles: Pd‐Catalyzed Domino Cyclization to Afford 1,2‐Fused Tricyclic Indole Scaffolds

Abstract: A concise method for the synthesis of 1,2-fused tricyclic indole scaffolds by domino cyclization involving a Pd-catalyzed Sonogashira coupling, indole cyclization, regio- and chemoselective N-1 acylation, and 1,4-Michael addition is reported. This method provides straightforward access to tetrahydro[1,4]diazepino[1,2-a]indole and hexahydro[1,5]diazocino[1,2-a]indole scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…. 120 Optimization of the reaction revealed that best results required use of Pd(OAc)2 (10 mol%) and PPh3 (40 mol%) as catalytic system, in the presence of an inorganic base (K2CO3, 2 equiv.) and a phase transfer catalyst (n-Bu4NBr, 2 equiv.)…”
Section: Palladium Catalyzed Functionalization / Annulation Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…. 120 Optimization of the reaction revealed that best results required use of Pd(OAc)2 (10 mol%) and PPh3 (40 mol%) as catalytic system, in the presence of an inorganic base (K2CO3, 2 equiv.) and a phase transfer catalyst (n-Bu4NBr, 2 equiv.)…”
Section: Palladium Catalyzed Functionalization / Annulation Cascadementioning
confidence: 99%
“…Scheme 39 Pd-catalyzed annulation of β-iodoacrylamides with allenyl stannanesIn 2015, Wang and co-workers reported a straightforward access to 1,2-fused tricyclic indoles 119 based on a Pd-catalyzed domino annulation sequence from N-sulfonylated (prop-2-yn-1yl)acrylamides 1w and substituted 2,2,2-trifluoro-N-(2iodophenyl)acetamides 118 (Scheme 40) 120. Optimization of the reaction revealed that best results required use of Pd(OAc)2 (10 mol%) and PPh3 (40 mol%) as catalytic system, in the presence of an inorganic base (K2CO3, 2 equiv.)…”
mentioning
confidence: 99%
“…N-Boc protection: Prepared from a modified literature procedure. 6 Indole-2carboxaldehyde (580 mg, 4.00 mmol, 1.0 equiv.) was taken up in THF (16 mL, 0.25M) in a 50 mL rbf.…”
Section: Tert-butyl 2-(dimethoxymethyl)-1h-indole-1-carboxylate [1o]mentioning
confidence: 99%
“…Due to the highly rotameric nature of 7a and to peak overlap, not all carbon signals could be located. IR (ATR, cm -1 ) 2959, 2931,2872,2246,1685,1642,1481,1432,1393,1336,1303,1172,1139,907,764,724,646 6,167.9,143.6,143.5,137.0,131.3,130.7,130.4,130.1,129.8,129.7,128.4,127.4,127.1,127.0,124.5,124.0,123.8 (q,J = 272.5 Hz),123.3,121.8,118.0,65.7,58.0,48.8,38.2,37.6,32.1,28.3,23.9. Major rotamer reported.…”
Section: Preparation Of N-methyl Thiourea Fragment (Rs)-7a and Catalmentioning
confidence: 99%
“…A plethora of indole‐fused polyheterocycles have been known to have a range of bioactivities, and there are several reported methods to access these various indole‐fused polyheterocycles. Most of these strategies focus on the synthesis of either 1,2‐polycyclic‐fused indoles or 2,3‐polycyclic‐fused indoles . Few methods, however, are available for the preparation of 1,2,3‐fused indole polyheterocycles by starting from N ‐functionalized indole derivatives, which results in a limited scope of possible products …”
Section: Introductionmentioning
confidence: 99%